Rice Pti1a Negatively Regulates RAR1-Dependent Defense Responses - Takahashi, Akira (American Society of Plant Biologists, 2007)
Tomato (Solanum lycopersicum) Pto encodes a protein kinase that confers resistance to bacterial speck disease. A second protein kinase, Pti1, physically interacts with Pto and is involved in Pto-mediated defense signaling. Pti1-related sequences are highly conserved among diverse plant species, including rice (Oryza sativa), but their functions are largely unknown. Here, we report the identification of a null mutant for the Pti1 homolog in rice and the functional characterization of Os Pti1a. The rice pti1a mutant was characterized by spontaneous necrotic lesions on leaves, which was accompanied by a series of defense responses and resistance against a compatible race of Magnaporthe grisea. Overexpression of Pti1a in rice reduced resistance against an incompatible race of the fungus recognized by a resistance (R) protein, Pish. Plants overexpressing Pti1a were also more susceptible to a compatible race of the bacterial pathogen Xanthomonas oryzae pv oryzae. These results suggest that Os Pti1a negatively regulates defense signaling for both R gene–mediated and basal resistance. We also demonstrated that repression of the rice RAR1 gene suppressed defense responses induced in the pti1a mutant, indicating that Pti1a negatively regulates RAR1-dependent defense responses. Expression of a tomato Pti1 cDNA in the rice pti1a mutant suppressed the mutant phenotypes. This contrasts strikingly with the previous finding that Sl Pti1 enhances Pto-mediated hypersensitive response (HR) induction when expressed in tobacco (Nicotiana tabacum), suggesting that the molecular switch controlling HR downstream of pathogen recognition has evolved differently in rice and tomato.